A Review on Elliptical Curve Crypto Graphing - Behera, Santosh; Behera, Sanjay (International Journal of Psychosocial Rehabilitation, 2025)
The elliptical crypto graphing curve (ECC) plays a significant position in today’s major public safety net. ECC is a faster and safer form of cryptography, like other common Cryptographic algorithms. The reliability advantages of ECC in the wireless Internet are addressed in this report. First of all, this paper introduces and evaluates the algorithm for various inputs for bit lengths. To further boost the safety level, a big question of maximal authentication is created and carried out based on the ECC algorithm. This paper doesn’t only rely on a single person, but on many people in our cryptographic threshold to decrypt our text. This network is safeguarded by Threshold Cryptography (TC). In this paper the ECC methodology is found to be more fitting than RSA. In the implementation of elliptic curve cryptography threshold cryptography (ECC-TC), this paper has explored and tested the three most efficient EC cryptographic algorithms and have developed the ability to use ECC-TC algorithms in different scenario of MANET. They equate both ECC-TC analysis and suggest an application appropriate for MANET. Finally, this paper has suggested a new approach for classified communication which reduces overhead communications to multiple documents at the same time.